Immobilization of acetylcholinesterase onto pyrrole-containing photocured thermosets - DEMİR, SERAP; ÇAKMAKÇI, EMRAH; OGAN, AYŞE (My University, 2023)
Acetylcholinesterase (AChE; EC 3.1.1.7) is a group of enzymes that catalyzes the hydrolysis of the neurotransmitter acetylcholine (ACh) into choline and acetate. AChE inhibition is commonly utilized as a biomarker for pesticides. In membrane based AChE biosensors the enzyme immobilization onto an electrode surface is of prime importance. In previous studies, conducting polymers-based supports have been used for the immobilization of AChE. In this study, a novel immobilization platform was developed. The simultaneous polymerization of pyrrole and functional thiol/ene monomers was performed to prepare conductive thermosets. AchE was covalently immobilized onto the membranes through the epoxy functional groups. After the immobilization process, the optimal temperature increased to 50 °C, displaying a better thermal stability and the optimum pH was elevated to 8.5. The activity of the immobilized enzyme was tested in the presence of several metals, and it was found that Cu2+ ions caused a noticable inhibition. After 10 cycles, the immobilized enzyme retained 51% of its original activity. In accordance with our results; the durability and the stability of the immobilized enzyme were improved. In future studies, the method applied here can be used in the design of an AchE biosensor.

Asetilkolinesteraz (AChE; EC 3.1.1.7), nörotransmiter asetilkolinin (ACh) kolin ve asetata hidrolizini katalize eden bir grup enzimdir. AChE inhibisyonu, pestisitler için biyolojik bir belirteç olarak yaygın olarak kullanılmaktadır. Membran temelli AChE biyosensörlerinde, elektrot yüzeyine enzimin immobilizasyonu oldukça önemlidir. AChE'nin immobilizasyonu için iletken polimerlerl de içeren pek çok farklı destek kullanılmıştır. Bu çalışmada, yeni bir immobilizasyon platformu geliştirilmiştir. Pirol ve tiyol-en monomerleri ile birlikte polimerleştirilerek iletken polimerik termosetler elde edilmesi planlanmıştır. AChE epoksi grupları üzerinden membrana immobilize edilmiştir. İmmobilizasyon işleminden sonra enzimin optimum sıcaklığı 50°C’ye çıkarak daha iyi bir termal kararlılık gösterirken, optimum pH değeri 8.5’a yükselmiştir. İmmobilize enzimin aktivitesi üzerine çeşitli metallerin etkisi araştırılmış ve Cu+2 iyonlarının önemli bir inhibisyona yol açtığı bulunmuştur. 10 döngüden sonra, immobilize enzimin başlangıç aktivitesinin %51'ine halen sahip olduğu belirlenmiştir. Sonuçlarımızla uyumlu olarak immobilize edilen enzimin kararlılığının ve dayanıklılığının arttığı görülmektedir. Gelecek çalışmalarda burada önerilen metod bir AChE biyosensör tasarımında kullanılabilir.
Asetilkolinesterazın pirol içeren fotokürlenmiş termosetlere immobilizasyonu
Keywords: Asetilkolinesteraz; Tiyol-en; Fotokürlenme; Enzim immobilizasyonu; Pirol; Acetylcholinesterase; Thiol-ene; Photocuring; Enzyme immobilization; Pyrrole